Characteristics and Categories of Fetal Heart Rate Tracings and Adverse Neonatal Outcomes at Term - Wiley, Rachel L.; Roberts, Aaron W.; Cagino, Kristen A.; Zullo, Fabrizio; Mendez-Figueroa, Hector; Chauhan, Suneet P. (American Journal of Perinatology, 2025)
This study aimed to compare characteristics and categories of fetal heart rate tracings (FHRT) among term (≥37.0 weeks) singletons without versus with composite adverse neonatal outcomes (CANO).For 15 consecutive months, retrospectively FHRT of all deliveries were characterized by obstetricians, who were blinded to maternal characteristics, intrapartum course, and neonatal outcomes. The inclusion criteria were nonanomalous singletons at term, who labored and had at least 20 minutes of FHRT. CANO included any of the following: Apgar score < 7 at 5 minutes, mechanical ventilation for > 6 hours, hypoxic ischemic encephalopathy, seizure, sepsis, bronchopulmonary dysplasia, intraventricular hemorrhage, necrotizing, enterocolitis, birth injury, meconium aspiration syndrome, or neonatal death. Positive likelihood ratios (PLR), with pre- and posttest probabilities, were calculated.Of the 5,160 deliveries during the study period, 3,166 (61.4%) met inclusion criteria, and 2,765 (87.3%) had between 20 and 120 minutes of FHRT reviewed. CANO occurred in 49 (1.5%) of the newborns. Three FHRT characteristics differed significantly among those without and with CANO—severe decelerations, tachycardia with any decelerations, or with severe decelerations. The PLR ranged from 1.60 to 5.96 for CANO, with posttest probabilities of CANO from 2.4 to 8.3%. Persistent category I within 20 to 120 minutes of delivery occurred with similar frequency among those without versus with CANO (11.5 vs. 8.2%; p = 0.472; PLR: 0.71). Presence of category II anytime occurred similarly for those without and with CANO (88.5 vs. 89.8%; p = 0.785; PLR: 1.01); category III, at any time, also occurred similarly in the two groups (0.8 vs. 2.0%; p = 0.319; PLR: 2.65).In our cohorts of term singletons, neither the characteristics nor the category of FHRT provided clinically meaningful discriminative capacity between newborns with versus without CANO.
Keywords: Apgar score; bradycardia; category I, II, or III; composite adverse neonatal outcomes; decelerations—late, variable, prolonged; diagnostic tests; hypoxic ischemic encephalopathy; likelihood ratio; tachycardia